PENGUATAN PERAN GURU TAMAN PENDIDIKAN AL-QUR’AN DALAM MENINGKATKAN MINAT SISWA MEMBACA AL-QUR’AN DENGAN TAJWID DI KELURAHAN ROMODONG INDAH - Tohir, Muhamad; Hevitria, Hevitria; Saputra, Adi (JURNAL AL-QAYYIMAH, 2025)
The Al-Qur'an Education Park in Romodong sub-district is experiencing problems in teaching and learning to read and write the Qur'an, this causes a problem that hinders the achievement of a goal that is to be achieved so that it requires community service activities in the Romodong sub-district community using the Real Work Lecture (KKN) scheme. carried out increased reading of the Koran. The aim of this activity is to train TPA teachers' abilities and understanding of implementing learning in accordance with students' learning interests. Helping to increase understanding of recitation material and practice for TPA students. As well as improving and developing the abilities of Romodong sub-district TPA teachers in delivering learning material for reading the Al-Qur'an that is not boring and easy to understand. The results of service activities provide additional insight, knowledge and skills to the teaching staff at the Romodong sub-district TPA. Cultivate passion and enthusiasm for learning spiritually in an effort to increase the ability to read the Al-Qur'an by presenting various recitation material and practicing little by little the knowledge of recitation.Keywords— Al-Qur'an, Interest, Reading Education Park